2021
DOI: 10.3390/ma14174759
|View full text |Cite
|
Sign up to set email alerts
|

Broadband Vibration Attenuation Achieved by 2D Elasto-Acoustic Metamaterial Plates with Rainbow Stepped Resonators

Abstract: This paper investigates the influences of nonperiodic rainbow resonators on the vibration attenuation of two-dimensional metamaterial plates. Rainbow metamaterial plates composed of thin host plates and nonperiodic stepped resonators are considered and compared with periodic metamaterial plates. The metamaterial plates are modelled with the finite element modelling method and verified by the plane wave expansion method. It was found that the rainbow metamaterial plates with spatially varying resonators possess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…A sensitivity analysis on absorber resonant frequencies reveals significant sensitivity in the stopband regions. Wei [17] reported the vibration attenuation of 2D rainbow metamaterial plates with spatially varying stepped resonators. It is found that rainbow resonators can lead to broader vibration attenuation bands compared to periodic resonators.…”
Section: Introductionmentioning
confidence: 99%
“…A sensitivity analysis on absorber resonant frequencies reveals significant sensitivity in the stopband regions. Wei [17] reported the vibration attenuation of 2D rainbow metamaterial plates with spatially varying stepped resonators. It is found that rainbow resonators can lead to broader vibration attenuation bands compared to periodic resonators.…”
Section: Introductionmentioning
confidence: 99%
“…Elastic/mechanical/acoustic metamaterial structures [ 1 , 2 , 3 ], generally composed of periodically arranged substructures in the form of sandwich structures [ 4 , 5 , 6 ], have special mechanical properties. It is a research hotspot in the fields of mechanics, materials, physics and engineering in recent years [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Phononic crystals and metamaterials have attractive potential in elastic wave manipulation and attenuation [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. They show promising advantages in the applications of negative refraction [ 2 , 3 ], acoustic cloaking [ 4 , 5 ], wave focusing [ 6 , 7 , 8 , 9 , 10 ], wave attenuation [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ], and vibration-mode tailoring [ 18 ]. The features of phononic crystals and metamaterials stem from Bragg scattering and local resonance, respectively [ 19 , 20 , 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was demonstrated that the width of the bandgap of metamaterials, i.e., the frequency range of wave attenuation, is expandable by structural parametric optimization [ 12 ]. It is worth mentioning that the frequency range of wave attenuation is expandable by adopting rainbow resonators [ 15 , 16 ]. In the past, the metamaterials were assembled by local mechanical resonators integrated into primary structures [ 12 , 25 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%